Impact of Re-engineering Human Resources on High Performance: An Empirical Research in the Central Statistical Organization / Ministry of Planning - Nabeel Talib, Omar; Rashed Musaheb , Mohsin (Journal of Economics and Administrative Sciences, 2024)
Two variables represent the research's central concept. Reengineering human resources is the first, and high performance is the second. By examining and elaborating on the offered factors, the research intends to diagnose the influence that the first variable (reengineering of human resources) and the second variable (high performance) have on each other. What is the status of the human resources re-engineering approach and its impact on high performance in the Central Statistical Organisation, and what is the extent of awareness and knowing the extent of contribution of the human resources re-engineering approach to upgrading work and achieving high performance? These are some of the key questions that were used to represent the main research problem. The researcher adopted the descriptive analytical approach in its completion with its theoretical and applied aspects. The researcher also designed a questionnaire according to several ready-made foreign standards, as the questionnaire included (50) items, the first variable consisting of four dimensions included (20) items, and the second variable consisting of five dimensions (30) paragraphs, which were distributed to a random sample of employees at various administrative levels and job positions, consisting of (208) employees at the headquarters of the Central Statistical Organization. A set of statistical methods were relied upon in testing hypotheses, which are (arithmetic mean, standard deviation, coefficient of variation, and simple linear regression) by using a set of statistical tools in the processing of research data available in ready-made statistical programs (SPSS.V21). Finally, the researcher presented several conclusions based on appeared in the practical side of the research.